Cytochrome C Peroxidase (Ccp) Is a Molecular Determinant of the Oxidative Stress Response in the Extreme Acidophilic Leptospirillum Sp Cf-1 - Levican-Jaque, G; Chavez-Rosales, R; Paillavil-Navarro, B (OXFORD UNIV PRESS, 2017)
Bioleaching processes are used to recover metals from sulfidic ores. Biofilm formation on ores is important for bioleaching because the attached microorganisms start the leaching process by concentrating ferric ions in the extracellular matrix. It has been shown that hydrogen peroxide is spontaneously generated on the surface of ores and that it negatively influences the growth and activity of microorganisms. However, the mechanism by which bioleaching microorganisms tolerate exogenous H2O2 as an adaptive trait remains elusive. Herein, we demonstrate that the gene yhjA, encoding a predicted periplasmic cytochrome c peroxidase (CcP), is important for the response to exogenously generated oxidative stress in the iron-oxidizing acidophilic bacterium Leptospirillum sp. CF-1. Our results show that yhjA is co-transcribed with the genes encoding the peroxide-responsive transcription regulator PerR and peroxiredoxin AhpC. CcP activity, but not yhjA mRNA level, significantly increased in response to hydrogen peroxide and ferric ion exposure, suggesting a post-translational regulation. In agreement with these results, challenging planktonic cells with hydrogen peroxide significantly increased their attachment to pyrite surfaces. In summation, our results suggest that CcP is important to cope with exogenous H2O2, thus favoring the early steps of attachment to mineral substrates.